2019
DOI: 10.1021/acsaem.9b01585
|View full text |Cite
|
Sign up to set email alerts
|

Realizing High Thermoelectric Performance in GeTe through Optimizing Ge Vacancies and Manipulating Ge Precipitates

Abstract: Recent vast reinvestigations on GeTe, a promising thermoelectric material at medium temperature, have triggered enormous enthusiasm in the thermoelectric community again. Intrinsically, GeTe, as a p-type semiconductor, possesses plenty of Ge vacancies, resulting in extremely high carrier concentration. Meanwhile, because of the vast off-stoichiometric Ge, both concomitant Ge precipitates and Ge vacancies will influence the electrical and thermal transport properties caused by phonons and carriers scattering. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 57 publications
3
53
0
Order By: Relevance
“…Through water quenching and annealing, Ge precipitates in several submicron scale were found in nearly homogenous distribution in the sample, which displays much lower lattice thermal conductivity compared to the sample without heat treatment. [ 48 ] By manipulating Ge precipitates and Ge vacancies as well as decreasing hole carrier concentrations through Cr doping effect, a higher ZT value is obtained in the Cr doped GeTe.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through water quenching and annealing, Ge precipitates in several submicron scale were found in nearly homogenous distribution in the sample, which displays much lower lattice thermal conductivity compared to the sample without heat treatment. [ 48 ] By manipulating Ge precipitates and Ge vacancies as well as decreasing hole carrier concentrations through Cr doping effect, a higher ZT value is obtained in the Cr doped GeTe.…”
Section: Resultsmentioning
confidence: 99%
“…A very recent study shows that heat treatment by quenching and annealing process could produce more uniformly distributed Ge precipitates, which even benefits the thermoelectric performance by provided all‐scale phonons scattering. [ 48 ] In addition, another research also demonstrated that those Ge precipitates have no apparent negative impact on the electronic transport properties. [ 49 ] Actually, the study of the effect of vacancies and precipitates on the transport properties of materials such as Zintls has been established to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…[ 38–40 ] Due to the similarly beneficial band structure and strong phonon anharmonicity with PbTe arising from the same chemical bonding mechanism, [ 41,42 ] comparable high peak ZTs ≈2 have continuously been reported in the system of GeTe. [ 29,43–56 ] One important difference between these two compounds is that GeTe undergoes the structural phase transition from the low‐temperature rhombohedral to the high‐temperature cubic phase at a critical temperature around 700 K. [ 57,58 ] The rhombohedral structure refers to a unit cell with parameters ( a = b = c and α = β = γ < 90°), belonging to the hexagonal crystal family. It can be regarded as a slightly distorted rock‐salt lattice along the [111] direction with a interaxial angle less than 90°.…”
Section: Figurementioning
confidence: 99%
“…[ 53 ] As is known, suppressing the Ge vacancies is essential to ensure high charge carrier mobility that will be beneficial to achieve a high power factor. [ 47,50,66,72 ]…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation